Beyond Illiteracy and Poverty: Theorizing the Rise in Black Women’s Incarceration - Mary V. Alfred; Dominique T. Chlup (Adult Education Research Conference, 2010)
This paper explores the impact of poverty and low literacy on the increase in Black women’s incarceration. Using critical race theory as a guiding framework, we present the argument that neoliberal policies of welfare reform and crime control laws are primary reasons for the increase. We emphasize gender-responsive strategies in planning programs for low-income, low-literate, and incarcerated women.